Insights into the chemical composition of the metal-poor Milky Way halo globular cluster NGC 6426 - Hanke, Michael; Koch-Hansen, Andreas (Arxiv, 2016)
We present our detailed spectroscopic analysis of the chemical composition of four red giant stars in the halo globular cluster NGC 6426. We obtained high-resolution spectra using the Magellan2/MIKE spectrograph, from which we derived equivalent widths and subsequently computed abundances of 24 species of 22 chemical elements. For the purpose of measuring equivalent widths, we developed a new semi-automated tool, called EWCODE. We report a mean Fe content of [Fe/H] = -2.34$±$0.05 dex (stat.) in accordance with previous studies. At a mean $α$-abundance of [(Mg,Si,Ca)/3 Fe] = 0.39$±$0.03 dex, NGC 6426 falls on the trend drawn by the Milky Way halo and other globular clusters at comparably low metallicities. The distribution of the lighter $α$-elements as well as the enhanced ratio [Zn/Fe] = 0.39 dex could originate from hypernova enrichment of the pre-cluster medium. We find tentative evidence for a spread in the elements Mg, Si, and Zn, indicating an enrichment scenario, where ejecta of evolved massive stars of a slightly older population polluted a newly born younger one. The heavy element abundances in this cluster fit well into the picture of metal-poor globular clusters, which in that respect appear to be remarkably homogeneous. The pattern of the neutron-capture elements heavier than Zn point towards an enrichment history governed by the r-process with only little -if any- sign of s-process contributions. This finding is supported by the striking similarity of our program stars to the metal-poor field star HD 108317.
Gesehen am 24.10.2017